(NmATEMATI^ESKIE OSNOWY KIBERNETIKI (B/s - (NlAPA(B, (NwALENTIN gRIGORXEWI^s ((NkIEW (B:s (NwI]A [KOLA(B,s, 1974)
(NsPISOK LIT(B.: (NS(B. 442 - 446s
Keywords: (NkIBERNETIKA (B-(NmATEMATI^ESKIE OSNOWYs